"It's this diversity that makes Australia such a unique country": nationalism in a multinational marketing campaign. Issue 1 (1st January 2022) - Cramer, Rahel
ABSTRACT: Multinational corporations use nationalism as a marketing tool to promote products. Vice versa, marketing facilitates positive images of the nation. The advertising of multinational corporations therefore covertly contributes to people's understanding of identity. It is against this background that this research investigates how the relationship between nation-states and multinational corporations is established in advertising discourse. Drawing on multimodal critical discourse analysis as a theoretical framework, this study examines a marketing campaign of the multinational supermarket chain Woolworths in Australia. The main research question is "How does advertising discourse establish a link between nation-states and multinational corporations?" To address this central question, this study investigates how (1) the world is represented in advertising discourse, (2) various imagined communities are represented in advertising discourse, and (3) Australia is represented as different from all other nations in the campaign. Findings suggest that banal forms of cosmopolitanism go hand in hand with banal forms of nationalism in the campaign. Under the guise of educating customers, these ideologies serve to promote consumption and brand the company as Australian.